Sustainability Reporting and Earnings Management: Systematic Literature Review - Danti Sagita; Intan Meutia; Hasni Yusrianti (Politeknik Ganesha Medan, 2025)
This study aims to examine the development of sustainability reporting (SR) and earnings management (EM). The researchers employed a structured literature review method, utilizing reputable electronic databases to gather data from 2016 to 2024, resulting in the selection of 32 studies based on inclusion and exclusion criteria. The findings of this study comprehensively present the developments, types of variables, measurements, and suggestions for future research related to sustainability reporting and earnings management. Research on SR and EM has shown a continuous increase from 2018 to 2024, with the non-financial sector being the most frequently studied. The most relevant and significant theories utilized in research are stakeholder theory, agency theory, and legitimacy theory. These theories are commonly employed to explain why companies engage in sustainability reporting. Types of variables related to SR include sustainability reporting, sustainability measures, sustainability disclosure, sustainability engagement, financial sustainability, corporate sustainability management, corporate, sustainable development, and corporate sustainability performance. Types of variables related to EM include earnings management, real earnings management, earnings quality, management earnings forecast, and earnings transparency. Measurement of SR variable is predominantly based on standard GRI Index, Sustainability Reporting Disclosure Index, and ESG scores. EM variable is measured using the effective tax rate and book-tax differences. This research contributes to the academic discourse and practical applications in the fields of sustainability reporting and earnings management, offering valuable insights for future studies in this area.